Answer:
base = 24 ft
height = 28 ft
Explanation:
first we have to identify the 2 equations that give us
h = b+4
h*b/2 = 336
Now let's replace the h with (b + 4)
(b+4)*b/2 = 336
(b^2+4b)/2 = 336
b^2 + 4b = 336*2
b^2 + 4b = 672
b^2 + 4b - 672 = 0
when we have an equation of the form Ax ^ 2 + Bx + C = 0
we can use bhaskara
(-B√(B^2-4AC))/2A
we replace with the values
(-4√(4^2-4*1*-672))/2*1
b1 = -4 + 52 /2 = 24
b2 = -4 - 52 /2 = -28
we can only use positive values
b = 24
to know the height we replace b with 24 in the equation of the beginning
h = b+4
h = 24+4
h = 28
to corroborate we can calculate the area and see if it gives us correct
h*b/2 = 336
28*24/2 = 336
672/2 = 336
336 = 336
correct